2014
DOI: 10.1007/s00345-014-1459-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of an elevated plasma fibrinogen level with cancer-specific and overall survival in prostate cancer patients

Abstract: Although our data show a significant association between an elevated plasma fibrinogen level and poor prostate cancer prognosis, they have to be interpreted cautiously. Limitations of the present study are caused by its retrospective design, the limited accuracy obtained using ROC curve analysis, and potential confounding factors like cardiovascular disease and inflammatory diseases that have not been accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…During the end of the clotting process, fibrinogen is converted enzymatically by thrombin to fibrin and subsequently to a fibrin‐based blood clot. Recently, several reports suggested that elevated preoperative fibrinogen was associated with the progression and prognosis of malignancies, including lung, cervical, breast, pancreatic, esophageal, prostate, renal cell, and colon cancers. Previous studies have shown that high preoperative fibrinogen is associated with poor survival in GC patients who underwent curative gastrectomy, but these studies enrolled all stage I‐III or I‐IV patients, and no study had focused on a subgroup analysis in stage I and N0 patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the end of the clotting process, fibrinogen is converted enzymatically by thrombin to fibrin and subsequently to a fibrin‐based blood clot. Recently, several reports suggested that elevated preoperative fibrinogen was associated with the progression and prognosis of malignancies, including lung, cervical, breast, pancreatic, esophageal, prostate, renal cell, and colon cancers. Previous studies have shown that high preoperative fibrinogen is associated with poor survival in GC patients who underwent curative gastrectomy, but these studies enrolled all stage I‐III or I‐IV patients, and no study had focused on a subgroup analysis in stage I and N0 patients.…”
Section: Discussionmentioning
confidence: 99%
“…With a focus on urological cancer, the out coming evidence supports the role of fibrinogen and D‐dimers as potential tumor markers in prostate and renal cancer. These two hemostasis parameters could also represent indicators of worse cancer‐specific and overall survival . Particularly for prostate cancer, more research has shown a possible tumor marker role for F1.2 and TAT .…”
Section: Introductionmentioning
confidence: 99%
“…These two hemostasis parameters could also represent indicators of worse cancer-specific and overall survival. [12][13][14][15][16][17] Particularly for prostate cancer, more research has shown a possible tumor marker role for F1.2 and TAT. 18,19 F1.2, similarly to fibrinogen, seems to be associated with higher prostate cancer stage, whereas TAT was found to be associated with the Gleason score.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The fibrinogen levels are increased because of tumor-associated cytokines or endogenous synthesis by tumor cells themselves in cancer patients. 16 The endogenous fibrinogen has a key role in promoting the growth of lung and prostate cancer cells through interaction with fibroblast growth factor. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 20 The patients with increased level of fibrinogen have a significantly poorer disease-free survival and cancer-specific survival. Thurner et al 16 found that there was a significant association between an elevated plasma fibrinogen level and poor cancer specific survival and overall survival in patients with prostate cancer. Caine et al 5 found the significant fall in fibrinogen level after radical prostatectomy 3 months and 12 months after the surgery.…”
Section: Discussionmentioning
confidence: 99%